Hubungan Kepuasan dan Motivasi Mahasiswa terhadap Kinerja Dosen di STKIP Ita Wotu Nusa: The Relationship between Student Satisfaction and Motivation to Lecturer Performance at STKIP Ita Wotu Nusa - Wokas, Amalia Hayuningtias; Rahabav, Patrisius; Rumfot, Sumarni (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
This study aims to identify the relationship between student satisfaction and motivation on lecturer performance at STKIP Ita Wotu Nusa. This study uses a quantitative approach with a descriptive method. The study population includes all students of STKIP Ita Wotu Nusa, with a sample of 162 students from three selected study programs. Data were collected through a validated questionnaire and analyzed using descriptive and inferential analysis. The results showed that student satisfaction did not have a significant correlation with lecturer performance, while student motivation had a positive and significant correlation, although its strength was weak. In addition, regression analysis showed that together student satisfaction and motivation were positively related to lecturer performance with a weak relationship. This study recommends improving teaching strategies and interactions between lecturers and students to improve student motivation and lecturer performance.